Impact of an Educational Program upon Nurses’ Knowledge and Practices Concerning Neurogenic Bladder Rehabilitation for Spinal Cord Injured Persons - badir, Raheem; Jaddoue, Batool (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: To determine the impact of an educational program on nurses’ knowledge and practices concerning neurogenic bladder rehabilitation for spinal cord injured persons through a follow-up approach each two months post program implementation for six months. Methodology: "Follow-up" longitudinal design by using time series approach of data analysis and the application of pre-post tests approach for the study and the control groups. The study was carried out at Ibn Al-Kuff hospital for (SCI) in Baghdad governorate from 5th of July 2010 to 15th of October 2011. To achieve the objectives of the study, a non-probability (purposive) sample of (60) nurses (males and females) were working in SCI units were selected. The sample is divided equally into study and control groups. A questionnaire format was used for data collection which consisted of (3) three parts (185) items, including their knowledge, practices, and demographic characteristics. Instrument validity was determined through content validity, by a panel of experts. Reliability of the instrument was determined through the use of Pearson correlation coefficient for the testretest approach, which is (0.92) for their knowledge and (0.88) for their practices. Analysis of data was performed through the application of descriptive statistics (frequency, percentage) and inferential statistics (mean of scores, relative sufficiency, Pearson correlation coefficient, t-test and one way analysis of variance and chi- square test). 71 Iraqi National Journal of Nursing Specialties, Vol. 25 (2) 2012 Results: The results of the study indicated that the nurses in study group benefited from the implementation of health education program, their knowledge and practices were adequately improved and developed. Recommendations: The study recommends that there is a need to conduct annual examinations for nurses to evaluate their nursing care for SCI persons, with a focus on the practical side, and not upgrading any of them if they did not pass the examination successfully.